2019
DOI: 10.1088/1742-6596/1402/2/022067
|View full text |Cite
|
Sign up to set email alerts
|

School management on the basis of character building in teaching learning process

Abstract: This study aims at presenting school management model based on character building in teaching learning process. This survey research was conducted for 450 students at elementary schools in Jakarta in Indonesia. Structural Equation Modeling (SEM) was used in analyzing data. Study result found that model hypothesized was a good fit for the data. Other findings confirmed that teaching learning process preparation, teaching learning process, and teaching learning process closing are positively correlated with char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The results of research in Indonesia and Malaysia showed that character education in schools was carried out programmatically, starting from the formulation of plans to evaluation (Karuniawati & Nadeak, 2021). In a study, learning preparation starting from prayer and checking the neatness of students' uniforms, the learning process by teaching teamwork, and closing the teaching and learning process by praying and greetings were positively correlated in character building (Marini et al, 2019). Character learning can also be carried out through an integration process in routine activities at school, exemplary, conditioning in other subjects, and school culture as a student learning environment (Lubis & Nasution, 2017;Sardiman, 2012).…”
Section: Exemplarymentioning
confidence: 99%
“…The results of research in Indonesia and Malaysia showed that character education in schools was carried out programmatically, starting from the formulation of plans to evaluation (Karuniawati & Nadeak, 2021). In a study, learning preparation starting from prayer and checking the neatness of students' uniforms, the learning process by teaching teamwork, and closing the teaching and learning process by praying and greetings were positively correlated in character building (Marini et al, 2019). Character learning can also be carried out through an integration process in routine activities at school, exemplary, conditioning in other subjects, and school culture as a student learning environment (Lubis & Nasution, 2017;Sardiman, 2012).…”
Section: Exemplarymentioning
confidence: 99%
“…This study states that character education is associated with the culture of the people who actualized and used as an approach (Nadlir, 2016;Nida, 2019). In line with that Sulistyaningsih find that the development of character education is done in the design, the realization and a series of measures tested the relationship between educators and students (Marini et al, 2019;Sulistyaningsih et al, 2018). But the majority of his research, the author has not integrate a reflection of the character education is done with the quality and effectiveness of the learning plan.…”
Section: Introductionmentioning
confidence: 76%
“…Among the indicators that are often put forward, that in people's lives, there are still many cases of community actions that are contrary to religious teachings. The existence of violence and violence carried out among youth, students and students is still widely reported in the mass media (Irwanto et al, 2018;Marini et al, 2019). Similar to immoral behaviuor are cases of pregnancy out of wedlock and the number of youths involved in drug use which greatly affects students' attitudes while in the school environment, this shows that there is an inadequate appreciation of the values of religious teachings in people's lives.…”
Section: Discussionmentioning
confidence: 99%
“…Science learning is an activity carried out by teachers and students to study forms and events related to the universe. Science learning is an interaction between learning components such as educators, students, learning tools or media in the form of teaching and learning activities to achieve predetermined goals and competencies (Irwanto et al, 2018;Marini et al, 2019). Science subjects are included in difficult subjects.…”
Section: Conceptual and Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation